2021
DOI: 10.1038/s41598-021-99593-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the JAZ gene family in turnip

Abstract: JAZ is a plant-specific protein family involved in the regulation of plant development, abiotic stresses, and responses to phytohormone treatments. In this study, we carried out a bioinformatics analysis of JAZ genes in turnip by determining the phylogenetic relationship, chromosomal location, gene structure and expression profiles analysis under stresses. The 36 JAZ genes were identified and classified into four subfamilies (ZML, JAZ, PPD and TIFY). The JAZ genes were located on 10 chromosomes. Two gene pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Tandem and segmental replication events were observed in the MsOSCA gene family (Figure 4A), indicating that gene replication was also the driving force for the expansion of MsOSCA gene family members. Previous studies have shown that gene pairs with high homology in the gene family may have collinearity, which makes them have similar biological characteristics and expression patterns (Jia et al, 2021). In the present study, we found that MsOSCAs had collinearity with Medicago truncatula and Arabidopsis, suggesting that they might have similar functions, which requires further investigation.…”
Section: Discussionsupporting
confidence: 46%
“…Tandem and segmental replication events were observed in the MsOSCA gene family (Figure 4A), indicating that gene replication was also the driving force for the expansion of MsOSCA gene family members. Previous studies have shown that gene pairs with high homology in the gene family may have collinearity, which makes them have similar biological characteristics and expression patterns (Jia et al, 2021). In the present study, we found that MsOSCAs had collinearity with Medicago truncatula and Arabidopsis, suggesting that they might have similar functions, which requires further investigation.…”
Section: Discussionsupporting
confidence: 46%
“…Multiple TIFY protein sequences were compared, and a phylogenetic tree was constructed using the maximum likelihood method. Based on the results of the phylogenetic tree and the classification of TIFY proteins in other species [ 23 25 ], the TIFY proteins were categorized into nine subfamilies, namely, JAZ I-VI, PPD, TIFY, and ZML (Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The JAZ gene family is present in a wide range of plants. There are 23 JAZs in A. thaliana [ 51 ], 15 in rice [ 52 ], 16 in maize [ 48 ], 36 in turnip [ 53 ], 30 in cotton [ 54 ], and 11 in grape [ 55 ]. We found that SLJAZ5 was located on chromosome 3; SLJAZ6 and SLJAZ7 on chromosome 6; SLJAZ8 on chromosome 7; SLJAZ9 , SLJAZ10 , SLJAZ11 , and SLJAZ12 on chromosome 8; SLJAZ13 on chromosome 9; SLJAZ14 on chromosome 11; and SLJAZ15 and SLJAZ16 on chromosome 12.…”
Section: Discussionmentioning
confidence: 99%